Attribution factors of chemistry anxiety: what are they? - Kamaruddin, Nurfariha (2015)
Chemophobia is supposedly to be known as chemistry anxiety. Chemistry anxiety will influence the development of holistic students to be as part of competent experts in scientific and technology arena in the near future. Chemistry anxiety that exist among science stream students at secondary school level tends to impairs performance and cause the low student enrollment in science field at the tertiary level. The attribution factors of chemistry anxiety that can be studied comprise of chemistry anxiety in learning, chemistry anxiety in evaluation and chemistry laboratory anxiety. Indeed, chemistry anxiety in learning aspect is anxious feeling that exists among students when they learn chemistry in classroom or laboratory while chemistry anxiety in evaluation is described as an arousal of undesirable feeling when sitting for assessment or test that related to chemistry subject and chemistry laboratory anxiety is fear of chemical substances or handling laboratory apparatus that perceived by the students when conducting experimental tasks. Determination of undesirable apprehension towards chemistry is required to be studied in order to discover preventive interventions that consequently help in cultivating science stream students’ interest towards chemistry.